Effect of postpolymerization method on the color stability of composite resins submitted to ultraviolet aging - Dos Santos, Paulo Henrique [UNESP]; De Souza, Fernando Isquierdo [UNESP]; Guedes, Ana Paula Albuquerque [UNESP]; Pavan, Sabrina (My University, 2012)
The aim of this research was to evaluate the effect of postpolymerization method on the color stability of resin-based composites. Samples of direct and indirect restorative materials were polymerized with two photo-curing units (Visio photo-curing oven system and LED Elipar Freelight 2). All samples were submitted to an initial chromatic analysis using a spectrometer and submitted to ultraviolet-accelerated artificial aging. The direct material showed less color change than the indirect material, independent of the photo-activation method used. Samples photo cured with the LED system showed less change than those photo cured with the Visio system. The postpolymerization oven did not improve the color stability of direct and indirect resin-based composites. © 2012 by Quintessence Publishing Co Inc.